Development of a twin-head infusion pump for micromixing - Sundra, Sargunan; Chin, Fhong Soon; Hiung, Hing Yap; Othman, Sheril Amira; Zainal, Nurfarina; Morsin, Marlia; Kian, Sek Tee (Penerbit UTHM, 2020)
Mixing is a crucial process in most of the industrial technology such as the operation of chemicals and fermentation reactors, combustion engines, polymer blends, and pharmaceutical formulations [1]. For handling a smaller volume of liquid, micromixing is a suitable method that can be applied. Micromixing (micromixer) is one of the microfluidic functions for mixing and blending liquids as precursors for biological process such as cell activation, enzyme reaction, and drug delivery system [2, 3]. There are several advantages of applying microfluidic device (micromixer) in the chemical technological processes such as processing accuracy, efficiency, minimum usage of reagents and ease of disposing of devices and fluids [3]. Basically, micromixers are categorised into passive and active micromixers. Passive micromixer consists of no moving parts and free from additional friction. It does not use external forces, fully dependent on molecular diffusion and chaotic advection for mixing process [4]. In contrast to active micromixers, external forces are applicable to active micromixers by implementing moving elements either within the microchannels, a time-variant, or a pressure field [5]. To create the pressure field differences for moving the liquid within the micromixer, an infusion pump is usually applied.